Pengelolaan Perpustakaan Sekolah melalui Penerapan Inventarisasi, Klasifikasi, Dan Preservasi Koleksi Untuk Meningkatkan Akses Dan Pemanfaatan Materi Bacaan - Indrahti, Sri (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2025)
School libraries play a crucial role in facilitating students' learning processes by providing access to diverse sources of information. However, at the Integrated Islamic Junior High School (IT) Al-Fikri, library management has yet to reach an optimal . To address this issue, outreach activities encompassing inventory, classification, and preservation of library book collections are undertaken, alongside socialization sessions for librarians and school staff on effective library management practices. These efforts aim to enhance the effectiveness and efficiency of school library management, thereby improving the quality of learning and access to information for students.